Anti‐neurochondrin antibody as a biomarker in primary autoimmune cerebellar ataxia—a case report and review of the literature. (7th December 2022) - Schwarzwald, Anina; Salmen, Anke; León Betancourt, Alejandro Xavier; Diem, Lara; Hammer, Helly; Radojewski, Piotr; Rebsamen, Michael; Kamber, Nicole; Chan, Andrew; Hoepner, Robert; Friedli, Christoph
Abstract: Background and purpose: Neuronal autoantibodies can support the diagnosis of primary autoimmune cerebellar ataxia (PACA). Knowledge of PACA is still sparce. This article aims to highlight the relevance of anti‐neurochondrin antibodies and possible therapeutical consequences in people with PACA. Methods: This is a case presentation and literature review of PACA associated with anti‐neurochondrin antibodies. Results: A 33‐year‐old man noticed reduced control of the right leg in May 2020. During his first clinic appointment at our institution in September 2021, he complained about gait imbalance, fine motor disorders, tremor, intermittent diplopia and slurred speech. He presented a pancerebellar syndrome with stance, gait and limb ataxia, scanning speech and oculomotor dysfunction. Within 3 months the symptoms progressed. An initial cerebral magnetic resonance imaging, June 2020, was normal, but follow‐up imaging in October 2021 and July 2022 revealed marked cerebellar atrophy (29% volume loss). Cerebrospinal fluid analysis showed lymphocytic pleocytosis of 11 x 10 3 /L (normal range 0–4) and oligoclonal bands type II. Anti‐neurochondrin antibodies (immunoglobulin G) were detected in serum (1:10, 000) and cerebrospinal fluid (1:320, by cell‐based indirect immunofluorescence assay and immunoblot, analysed by the EUROIMMUN laboratory). After ruling out alternative causes and neoplasia, diagnosis of PACA was given and immunotherapy (steroids and cyclophosphamide) was started in January 2022. In March 2022 a stabilization of disease was observed. Conclusion: Cerebellar ataxia associated with anti‐neurochondrin antibodies has only been described in 19 cases; however, the number of unrecognized PACAs may be higher. As anti‐neurochondrin antibodies target an intracellular antigen and exhibit a mainly cytotoxic T‐cell‐mediated pathogenesis, important therapeutic implications may result. Because of the severe and rapid clinical progression, aggressive immunotherapy was warranted. This case highlights the need for rapid diagnosis and therapy in PACA, as stabilization and even improvement of symptoms are attainable.